Implementasi CorelDRAW X7 Dalam Pengembangan Corporate Identity Sebagai Media Promosi - Oktaviani, Defani; Darsiti (Jurnal Multimedia dan Teknologi Informasi (Jatilima), 2024)
This research aims to implement CorelDRAW X7 in developing the corporate identity of Kompepar Giriharja as an effective promotional medium. Kompepar Giriharja is a tourism promotion organization in Jelekong Tourism Village, West Java, which requires branding to showcase their identity with a more modern and attractive appearance. The research methods include SWOT analysis, literature study, interviews, observation, and document analysis. The logo design process involves systematic stages from research to digitalization using CorelDRAW X7. The research results in a logo design that combines lotus flower motifs and traditional Indonesian batik ornaments, with a dominant dark red color symbolizing courage and cultural richness. This logo is then implemented on various promotional media such as social media, outdoor advertising, stationery, and merchandise. This study demonstrates that the use of CorelDRAW X7 is effective in developing a strong and consistent corporate identity, and can enhance brand awareness and promotional strategies for Kompepar Giriharja as a tourism organization in West Java.